PRDM12 Is Transcriptionally Active and Required for Nociceptor Function Throughout Life - Kokotović, Tomislav; Langeslag, Michiel; Lenartowicz, Ewelina M.; Manion, John; Fell, Christopher W.; Alehabib, Elham; Tafakhori, Abbas; Darvish, Hossein; Bellefroid, Eric J.; Neely, G. Gregory; Kress, Michaela; Penninger, Josef M.; et al. (Frontiers in Molecular Neuroscience, 2021)
PRDM12 is a key developmental transcription factor in sensory neuronal specification and survival. Patients with rare deleterious variants in PRDM12 are born with congenital insensitivity to pain (CIP), due to a complete absence of a subtype of peripheral neurons that detect pain. Here, we report two additional CIP cases with a novel homozygous PRDM12 variant. To elucidate the function of PRDM12 during mammalian development and adulthood we generated temporal and spatial conditional mouse models. We find that PRDM12 is expressed throughout the adult nervous system. We observed that loss of Prdm12 during mid-sensory neurogenesis but not in adult leads to reduced survival. Comparing cellular biophysical nociceptive properties in developmental and adult-onset PRDM12 deletion mouse models we find that PRDM12 is necessary for proper nociceptive responses throughout life. However, we find that PRDM12 regulates distinct transcriptional programs depending on age. Together, our results implicate PRDM12 as a viable therapeutic target for specific pain therapies even in adults. Keywords PRDM12, TRPV1, capsaicin, pain, nociception, CIP, dorsal root ganglia